Durability of Mortar Made with Fine Glass Powdered Particles - Rosemary Bom Conselho Sales; Fernando Augusto Sales; Enio Pazini Figueiredo; White José dos Santos; Nelcy Della Santina Mohallem; Maria Teresa Paulino Aguilar (Advances in Materials Science and Engineering)
Different studies investigate the use of waste glass in Portland cement compounds, either as aggregates or as supplementary cementitious materials. Nevertheless, it seems that there is no consensus about the influence of particle color and size on the behavior of the compounds. This study addresses the influence of cement replacement by 10 and 20% of the colorless and amber soda-lime glass particles sized around 9.5 μm on the performance of Portland cement mortars. Results revealed that the partial replacement of cement could contribute to the production of durable mortars in relation to the inhibition of the alkali-aggregate reaction. This effect was more marked with 20% replacement using amber glass. Samples containing glass microparticles were more resistant to corrosion, in particular those made of colorless glass. The use of colorless and amber glass microparticles promoted a reduction in wear resistance.